The effect of soy isoflavones on egg quality and bone mineralisation during the late laying period of quail - Şahin, Nurhan; Onderci, M.; Balci, T. A.; Cikim, G.; Şahin, Kazım; Küçük, Ömer (Taylor & Francis Ltd, 2007)
1. Soy isoflavones play a role in calcium and bone metabolism. Poor egg quality, skeletal abnormalities and architectural deterioration of bone tissue are common problems under hot climate conditions and with increased age in poultry. 2. In this study, we investigated the effects of soy isoflavone supplementation on egg production, egg quality, bone mineral density (BMD), levels of osteocalcin (OC), vitamin D, calcium (Ca), phosphorus (P) and alkaline phosphatase (ALP) activity in quail (Coturnix coturnix japonica) during the late laying period. 3. The birds (n = 180; 28 weeks old) were randomly assigned to 6 treatment groups consisting of 6 replicates of 5 birds each in a 2 x 3 factorial arrangement of treatments (temperatures, soy isoflavone concentration). Birds were kept in wire cages in a temperature-controlled room at either 22 degrees C (thermo-neutral, TN) or 34 degrees C (heat stress, HS) for 8 h/d (09:00 to 17:00 h; until the end of the study) and fed either on a basal (control) diet or on the basal diet supplemented with either 400 or 800 mg of soy isoflavones/kg of diet. 4. Heat exposure reduced feed intake, egg production, egg quality, BMD, OC, vitamin D, Ca, P and ALP when the basal diet was given. Feed intake, egg production and egg weight were not affected, while eggshell thickness and eggshell weight increased in soy isoflavone-supplemented quails reared under TN conditions. However, feed intake, egg production, egg weight, eggshell thickness, eggshell weight and Haugh units were positively influenced by soy isoflavone supplementation in HS groups for quail during the late laying period. Bone mineral density, serum OC, vitamin D, Ca, P levels and ALP activity were significantly improved by soy isoflavone supplementation in both the TN and HS groups in quail during the late laying period. 5. Soy isoflavone supplementation of basal diet significantly improved egg quality and bone mineralisation in quail during the late laying period.
Keywords: Tyrosine Kinase Inhibitors; Silicate Inositol Complex; Phyto-Estrogens; Genistein; Calcium; Strength; Protein; Phytoestrogens; Shell; Hens